Professores enquanto membros de categorias profissionais: um estudo sobre identificação e envolvimento com o trabalho no meio público - Alberti, Ricardo (2020)
The self-identification with a professional category is a sum of personal identity and social identification (Mael and Ashforth, 1992), as well as involvement with work or the degree to which the work situation is central to the person and to yours identity (LAWLER ; HALL, 1970, p. The objective of this study is to verify and identify what are the relations between identification and involvement with the work of teachers from public and municipal schools that use the Item Response Theory. To this end, an applied and descriptive research was carried out, based on the quantitative method using data collection and a personalized questionnaire structured around the following steps: Oliveira's Organizational Identification Scale (OIS) (2008), Work Involvement Scale (WIS) by Siqueira (2008) and the Visual Diagram of Organizational Identity Measurement by Bergami and Bagozzi (2000), validated by Faller (2017) in Brazil. Altogether, 505 teachers attended this study from 44 public elementary schools in the municipality of Santa Maria - RS. The collected data were analyzed using descriptive statistics, the Item Response Theory (IRT) through the Gradual Response Model (GRM). The main results demonstrated that OIS and WIS can be analyzed using the IRT of the GRM. The average index of identification with a professional category found through OIS is 3.22, that teachers have their identification with the professional category supported by crimes and values or was created in the long term in their interaction with other teachers and experience in the environment school. A WIS shows an average of 4.60, demonstrating that the values show a certain indifference or distrust, but in one of the questionnaires as answers they represent a positive degree of involvement with the work. In the Visual Diagram of Organizational Identity Measurement, the results show an average of 5.05, which demonstrates that teachers have a positive index of identification with a professional category. This study contributed to expand the knowledge about the concepts of construction and information gathering with teachers. It is believed that this work can serve as a basis to raise the indices of identification with a professional category and involvement with the work.